Generative AI in ELT: Readiness and Concerns of Badung EFL Teachers - Nyudak, Geovenda; Made Hery Santosa; Ni Putu Era Marsakawati; Putu Susrini (Institut Agama Islam Negeri Palopo, 2025)
This study examines the readiness and concerns of junior high school English as a Foreign Language (EFL) teachers in Badung, Bali, regarding the integration of Generative Artificial Intelligence (GenAI) into English Language Teaching (ELT). Using an explanatory sequential mixed-methods approach, the research involved 165 teachers who completed a survey adapted from Aydin and Tasci’s E-Learning Readiness Model and followed by interviews analyzed through the Concerns-Based Adoption Model (CBAM). Quantitative findings reveal that 87.3% of teachers were at moderate to high levels of readiness, particularly in the dimensions of Technology and Innovation. The People Factor scored lowest, indicating limited institutional support and training. Teachers also expressed strong personal motivation (Self-Development Factor), although hindered by budgetary and structural challenges. Qualitative analysis revealed that most participants had progressed beyond the Awareness stage of CBAM and were actively utilizing GenAI tools in instructional planning. Some even reached advanced stages such as Collaboration and Refocusing. However, ethical-pedagogical concerns emerged, particularly regarding students’ dependence on AI. The findings underscore the importance of tailored training, targeted policy support, and ethical guidance to ensure the successful and sustainable integration of GenAI in English Language Teaching (ELT).